Development of Augmented Reality Based Student Worksheet (LKPD) on Sensory System Material - Fanny Adha Cyntia Tarigan; Miza Nina Adlini (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
In this digitalization era, there has been significant progress in the field of information and communication technology. 21st century learning is a consequence of societal progress that continues over time .The objective of this study is to create an Augmented Reality Based Student Worksheet for the purpose of enhancing the biology learning experience specifically for the sensory system topic. The research was conducted at Gema Buwana Tembung High School in the eleventh grade classroom. This study employed the Research and Development (R&D) methodology and a 4D model, which was implemented in only three stages: Define, Design, and Develop. The data collection methodologies employed included expert validation sheets, as well as answers from teachers and students. The research findings demonstrated a material validation rate of 92.7% and a media validation rate of 95.3% in the "very valid" category. The teacher's response yielded a 97% success rate, while the student response consisted of 21 responses and was classified as highly practical. The implementation of N-gain in high school resulted in a total score of 34.22, which was then averaged to 0.628 in the effective category. The N-gain value is calculated by taking the average of the pretest and posttest scores. The results indicate that the creation of an Augmented Reality-based Learning Kit for Practical Demonstrations og LKPD effectively captures students' attention and enhances their motivation to learn about sensory systems